Conceptual Framework: Semi-PSS for Sustainable Decommissioning of Offshore Platforms in Malaysia - Na, Kai Lun (2011)
For many of the offshore jacket structures in Malaysia, their design lives of 25-30 years is approaching the end, signifying the urgent implementation of decommissioning efforts. While current regulatory guidelines strongly recommend complete removal of the structures, in view of sustainability issues, other options of decommissioning should not be overlooked. As a way forward, this paper suggests an approach of reusing offshore jacket platforms as an opportunity to derive economic and/or scientific benefits. To utilize a structure beyond its design life, a thorough control of the structural safety must be executed. Integrating a risk-based structural assessment, weighting factors and the concept of hazard functions, the approach gauges the failure probabilities and risk events involved in the reusing of redundant offshore platforms. The principles of a risk-based structural assessment are thus described and the proposed conceptual framework is illustrated, linking the operational and structural risks in connection with reusing of an offshore jacket structure. This semi-probabilistic support system (Semi-PSS) provides a valuable outline in improving the selection of appropriate platforms to be refurbished and transformed into livable hubs